Biosimilar G-CSF based mobilization of peripheral blood hematopoietic stem cells for autologous and allogeneic stem cell transplantation - Schmitt, Michael; Publicover, Amy; Orchard, Kim H; Görlach, Matthias; Wang, Lei; Schmitt, Anita; Mani, Jiju; Tsirigotis, Panagiotis; Kuriakose, Reeba; Nagler, Arnon (Theranostics, 2014)
The use of granulocyte colony stimulating factor (G-CSF) biosimilars for peripheral blood hematopoietic stem cell (PBSC) mobilization has stimulated an ongoing debate regarding their efficacy and safety. However, the use of biosimilar G-CSF was approved by the European Medicines Agency (EMA) for all the registered indications of the originator G-CSF (Neupogen®) including mobilization of stem cells. Here, we performed a comprehensive review of published reports on the use of biosimilar G-CSF covering patients with hematological malignancies as well as healthy donors that underwent stem cell mobilization at multiple centers using site-specific non-randomized regimens with a biosimilar G-CSF in the autologous and allogeneic setting.
Gesehen am 27.10.2020